Diffusion dynamics in Pinus sylvestris Kraft impregnation: Effect of deacetylation and galactoglucomannan degradation - Montagna, Pablo N. (2013)
During the impregnation stage of a Kraft cooking, dynamic changes occur in wood properties due to the alkali action. Particularly, its ion transport capacity, the effective capillary cross sectional area (ECCSA), is changed due to chemical reactions and swelling. In this work, the ECCSA in the transverse wood direction has been determined for Pinus sylvestris on the basis of the analogy between capillarity and electrical conductivity. Results show that the behavior of ECCSA can be associated with (a) the degree of removal of native acetyl groups and (b) the galactoglucomannan (GGM) losses due to peeling/stopping reactions and alkaline hydrolysis. Kinetic expressions for both reactions were discussed and a correlation between the ECCSA and both acetyl and GGM contents was established.